Funds Based On Sharia Free - Nur Hidayah; Sri Masyuli Manullang; Dewi Julianti Sukma; Siti Fadillah Hafsah (Proceeding International Seminar of Islamic Studies, 2019)
The use of sharia-based financial instruments, especially matters related to debt will have an impact on the company's financial structure as well as conventional financial instruments, but the difference is from the concept side which will ultimately affect the calculation formulation that is different from conventional. So there are many differences in Islamic finance with conventional finance. Various financial indicators, such as the total value of assets and the amount of third party funds raised, continued to increase. Likewise, the quality of performance illustrated by the profits recorded by banks and Islamic finance units also experienced positive growth. M enggeliang its activities sharia banking in Indonesia can not be separated from the increased level of public trust to access the services of Islamic banking services. This can at least also be illustrated by the location of sharia banking offices and sharia financing units which are spread in almost all regions of the country to all over Indonesia . Compared with conventional banking, Islamic banking has the distinction very basic ie not m enaruh money as a commodity in trade, the determination of interest rates in the banking transaction is strictly prohibited kar ena usury, no element of time value of money and the remuneration for the use of funds m elaksanakan prin sip profit sharing. In order to share education and Perlin dams to the nasabh need for ana lisa on the principles of sharia in Islamic banking practices.